Soldering and packaging study for an optical filter required for high resolution earth observation space missions - Kepper, Mariia; Ribes-Pleguezuelo, Pol; Hornaff, Marcel; Beckert, Erik; Eberhardt, Ramona; Pranyies, Pascal; Toubhans, Isabelle; Descours, Francis; Tuennermann, Andreas (PHOTOPTICS 2019 - Proceedings of the 7th International Conference on Photonics, Optics and Laser Technology, 2019)
The goal of our study is to optimize the packaging process of an optical sensor module under the space mission requirements. The intention of the project is to develop a generation of optical sensor modules avoiding conventional organic adhesives (standard used technologies). The sensor module, designed by Sodern, consists of three parts: the sensor, the filter frame and the filter. The Solderjet Bumping is planned to be used for assembling KOVAR(29 % Ni, 17 % Co, 54 % Fe) and N-BK10 (Borosilicate-Kronglas, Schott glass) and for assembling KOVAR and KOVAR materials, chosen for this application, and creation of a strong bond between these materials, which should withstand the harsh environmental space conditions.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Earth Observation; Optical Filter; Satellite; Solderjet Bumping Technique; Space